2023
DOI: 10.3390/bios13030366
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Photoelectrochemical Immunoassay Strategy Based on Bi2S3/Ag2S for the Detection of the Inflammation Marker Procalcitonin

Abstract: As an inflammatory marker, procalcitonin (PCT) is more representative than other traditional inflammatory markers. In this work, a highly efficient photoelectrochemical (PEC) immunosensor was constructed based on the photoactive material Bi2S3/Ag2S to realize the sensitive detection of PCT. Bi2S3 was prepared by a hydrothermal method, and Ag2S quantum dots were deposited on the ITO/Bi2S3 surface via in situ reduction. Bi2S3 is a kind of admirable photoelectric semiconductor nanomaterial on account of its moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Therefore, the influence of mTiO 2 /Ag 2 S heterojunction formation on the photoelectric performance was investigated. The UV-visible absorption spectra in Figure 2 a depict the light-capturing abilities of Ag 2 S, mTiO 2 and mTiO 2 /Ag 2 S. It can be observed that TiO 2 exhibits significant absorption capability in the ultraviolet region, with an absorption edge at approximately 390 nanometers, while Ag 2 S demonstrates remarkable absorption in both the ultraviolet and visible light regions [ 34 , 35 ]. In contrast, upon Ag 2 S modification on the surface of mTiO 2 , there is a clear absorption in the visible light region.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the influence of mTiO 2 /Ag 2 S heterojunction formation on the photoelectric performance was investigated. The UV-visible absorption spectra in Figure 2 a depict the light-capturing abilities of Ag 2 S, mTiO 2 and mTiO 2 /Ag 2 S. It can be observed that TiO 2 exhibits significant absorption capability in the ultraviolet region, with an absorption edge at approximately 390 nanometers, while Ag 2 S demonstrates remarkable absorption in both the ultraviolet and visible light regions [ 34 , 35 ]. In contrast, upon Ag 2 S modification on the surface of mTiO 2 , there is a clear absorption in the visible light region.…”
Section: Resultsmentioning
confidence: 99%
“…Quantum dot-modified electrodes exhibit a change in photocurrent response, which successfully translates to analyte quantification. For example, the photocurrent generated by Ag 2 S quantum dot-modified Bi 2 S 3 /ITO electrodes allows the detection of picogram levels of PCT [ 80 ]. (iv) Electrochemically active redox couple molecules serve as promising biomarker labels.…”
Section: Strategies For Electrochemical Sepsis Sensorsmentioning
confidence: 99%
“…This sandwich-type Ab1/PCT/An2-non-noble OER catalyst architecture ( Figure 8 ) achieved the LOD of 0.33 pg mL −1 . The photoelectrochemical method was also applied for the design of a PCT sensor, with the use of a Bi 2 S 3 /Ag 2 S catalyst for the production of photocurrent [ 80 ]. Owing to the specific attraction between the antigen and a modified electrode, photocurrent intensity was found to decrease owing to the electron transfer hindrance effect.…”
Section: Electrochemical Detection Of Sepsis Biomarkersmentioning
confidence: 99%
“…As expected, a signal-enhanced immunosensor can be achieved by amplifying the photocurrent signal through the formation of a sandwich immunostructure, and the photocurrent was linear with the common logarithm of CYFRA21-1 ranging from 100 fg mL −1 to 50 ng mL −1 , with a LOD of 56 fg mL −1 . Zhao et al [63] established a PECI method based on the energy level matching principle of Bi 2 S 3 and Ag 2 S to realize the sensitive detection of procalcitonin (Figure 8d). This admirable platform shows a good linear range of 0.5 pg mL −1 -50 ng mL −1 and a low detection limit of 0.18 pg mL −1 .…”
Section: Photoelectrochemical Immunoassaysmentioning
confidence: 99%
“…[60] Copyright 2019, American Chemical Society. The sensitivity of the PECI sensor was improved by copper in situ deposition signal amplification (b) [61] , heterojunction modification (c) [62] , and energy level matching principles (d) [63] . Copyright 2019, Royal Society of Chemistry.…”
Section: Fluorescent Immunoassaysmentioning
confidence: 99%